Analisis Makna serta Diksi Pada Puisi “Padamu Jua” Karya Amir Hamzah - Rahmawati Rahmawati (Concept: Journal of Social Humanities and Education, 2022)
This study aims to discuss the hidden meaning in the text of the poem "Padamu Jua" by Amir Hamzah through discussion and exposure in terms of Hermeneutics and also examines interesting diction in the text of the poem. The hermeneutical theory is used to interpret the meaning of the poem. This study also uses a descriptive qualitative research model. The data subject of this study is a literary work of poetry with research data in the form of quoted words whose meaning and diction are analyzed using a hermeutical approach. Diction is word choice. That is, we choose the right words to convey an idea and accuracy. The role of diction in poetry is very important because in poetry words are everything. In fact, for the type of imaginary poetry as stated by Sapardi Djoko Damono. The data collection technique in this article is the first to analyze the meaning of perbait with a hermeneutical approach, the second to analyze and look for the interesting diction in the poem "Padamu Jua" by Amir Hamzah and the third to present the data results in descriptive form.